THE IMPLEMENTATION STATUS AND CHALLENGES OVER LAND UTILIZATION PROJECTS, PROVIDING ECOLOGICAL AND ECONOMICAL BACKGROUND ON CROP ROTATION AND LAND ORGANIZATION - Atamaniuk, O. P. (Землеустрій, кадастр і моніторинг земель, 2013)
The modern state of land development, providing ecological and economical back‐ ground on crop rotation and land organization, has been analyzed. Features and is‐ sues of the utilization projects introduction mechanism have been clarified. An effec‐ tiveness of proactive measures to accelerate the utilization projects introduction pro‐ cess has been demonstrated.